2020
DOI: 10.1177/0022429420982525
|View full text |Cite
|
Sign up to set email alerts
|

Is Music Teacher Professional Development Becoming More Effective? Evaluating Practice and Policy in the United States, 1993–2012

Abstract: The purpose of this study was to evaluate music teacher professional development (PD) practice and policy in the United States between 1993 and 2012. Using data from the nationally representative Schools and Staffing Survey (SASS) spanning these 20 years, I examined music teacher PD participation by topic, intensity, relevance, and format; music teachers’ top PD priorities; and the reach of certain PD-supportive policies. I assessed these descriptive results against a set of broadly agreed-on criteria for “eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 51 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…While the teachers’ needs, perceptions, preferences, and motivations of PD are important when designing and evaluating PD programs, there is a need for continued evaluation, consideration, and inclusion of the criteria that define “high-quality PD.” Results suggest that music educators are experiencing an abundance of music-specific PD that is content-rich, evidence-based, embedded, and coherent to policy, standards, teacher needs, and preferences. These findings corroborate with previous research regarding music-specific PD that is focused on content needs due to the broad music teaching certificate and alternative music classrooms where teachers may be teaching unfamiliar musical content (Grieser & Hendricks, 2018; May et al, 2017; West, 2020).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…While the teachers’ needs, perceptions, preferences, and motivations of PD are important when designing and evaluating PD programs, there is a need for continued evaluation, consideration, and inclusion of the criteria that define “high-quality PD.” Results suggest that music educators are experiencing an abundance of music-specific PD that is content-rich, evidence-based, embedded, and coherent to policy, standards, teacher needs, and preferences. These findings corroborate with previous research regarding music-specific PD that is focused on content needs due to the broad music teaching certificate and alternative music classrooms where teachers may be teaching unfamiliar musical content (Grieser & Hendricks, 2018; May et al, 2017; West, 2020).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…These statistics provide only a sliver of the complexities associated with the challenges facing district administrators and teachers. West (2021) described how the era of high-stakes testing has relegated the arts to noncore status, despite being supported as a key component of a well-rounded education by most Americans. The decision to start these programs was not based on any intrinsic potential for music to enhance the lives of the students or enrich the school culture, but for nonmusical reasons such as supporting athletic games, improving social distancing in academic classes, or housing specific groups of students.…”
Section: Discussionmentioning
confidence: 99%
“…They would have benefited from targeted, professional development geared toward their specific teaching contexts, with site-specific support (Johnson et al, 2019). Furthermore, professional development scholars suggest that informal conversations among colleagues may also be effective professional development (Brewer & Rickels, 2014; West, 2021). Participants’ ability to have these conversations was limited due to their isolation, but what little they had was very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is reasonable to assume music teachers would benefit from PD's political and legal position in the education system, extant evidence suggests otherwise. West (2021) examined PD practices among nationally representative samples of music teachers between 1993 and 2012, a period marked by the standards-and-accountability movement in the United States and before and after the 2002 passage of NCLB. He concluded that although access to music-specific PD had markedly improved over that 20-year period, music teachers reported a lack of consistent participation in collaborative PD experiences, such as mentoring and coaching; low levels of sustained PD; middling perceptions of PD's utility to practice; little influence over PD content; and limited provision of PD funding and release time.…”
Section: Related Literaturementioning
confidence: 99%
“…In response, music education researchers have sought to delineate music-specific principles of high-quality PD, drawing on PD effectiveness frameworks in general education (e.g., Darling-Hammond et al, 2017;Desimone, 2009). Scholars have held that PD ought to be musical, grounded in teachers' school contexts, involve teachers in social exchange with their peers, be supported by and aligned with school and district policy, and take place over extended periods of time (e.g., Barrett, 2006;Bautista et al, 2017;NAFME, 2015;Stanley et al, 2014;West, 2021;West & Bautista, 2022). Qualitative and quantitative evidence suggests that music teachers are likelier to engage in PD that meets these effectiveness standards (Wesolowski et al, 2022;West, 2020).…”
Section: Related Literaturementioning
confidence: 99%